Value Monism, Richness, And Environmental Ethics - Kelly, Chris (Les ateliers de l'éthique / The Ethics Forum, 2014)
The intuitions at the core of environmental ethics and of other neglected value realms put pressure on traditional anthropocentric ethics based on monistic value theories. Such pressure is so severe that it has led many to give up on the idea of monistic value theories altogether. I argue that value monism is still preferable to value pluralism and that, indeed, these new challenges are opportunities to vastly improve impoverished traditional theories. I suggest an alternative monistic theory, Richness Theory, and show how it provides an opportunity to capture the needs of both environmental ethics and of our traditional ethics.